A Systematic Literature Review of Business Process Management in SMEs: Key Benefits and Challenges - Sari, Putri Pradnyawidya; Wahyudin, Asep; Dewi Dirgantari, Puspo (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
This systematic literature review (SLR) examines the function of Business Process Management (BPM) in augmenting the operational effi cacy of Small and Medium-sized Enterprises (SMEs). BPM methodologies can aff ord substantial advantages, encompassing enhanced operational productivity, increased customer satisfaction, and improved market fl exibility. Nonetheless, SMEs frequently encounter obstacles such as constrained resources, insuffi cient expertise, and resistance to change when endeavoring to implement BPM frameworks. This review consolidates fi ndings from empirical investigations regarding the principal advantages and challenges of BPM in SMEs, emphasizing the necessity for customized BPM solutions that take into account the distinctive characteristics of SMEs. The review further delineates gaps within the existing literature, particularly in relation to the longitudinal impacts of BPM adoption and the assimilation of digital technologies within BPM practices. Subsequent research should concentrate on formulating cost-eff ective, scalable BPM frameworks and investigating the convergence of BPM and digital transformation for SMEs.